Art Medium and Art Infrastructure Development in Contemporary Indonesian Art - A. Rikrik Kusmara (ITB Journal Publisher, LPPM ITB, 2013)
This research review Indonesian contemporary artists that used the various media in the presentation in his works over the years since 2000 until now. Survey at Pameran Besar Indonesia